International trade and developing countries : bargaining coalitions in the GATT & WTO - Narlikar, Amrita (Routledge/RIPE series in global political economy. Routledge/RIPE studies in global political economy, 2003)
This book analyses the much-needed and vastly under-studied subject of bargaining coalitions of developing countries in the GATT and WTO.